2020
DOI: 10.3390/ijerph17207395
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Graph Analysis of Human Health Research Related to Climate Change

Abstract: In order to explore the development status, knowledge base, research hotspots, and future research directions related to the impacts of climate change on human health, a systematic bibliometric analysis of 6719 published articles from 2003 to 2018 in the Web of Science was performed. Using data analytics tools such as HistCite and CiteSpace, the time distribution, spatial distribution, citations, and research hotspots were analyzed and visualized. The analysis revealed the development status of the research on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Actually, search results in WoS are not presented by author, year, subject and document types like Scopus, but also by institutions and countries [ 32 ], which is convenient for scholars to analyze the distribution of the research organizations. Moreover, WoSCC has been used as a data source in some previous bibliometric studies [ 33 , 34 , 35 , 36 , 37 , 38 ], which further proves its feasibility especially in the natural science domains. The study design was shown in Figure 1 .…”
Section: Methodsmentioning
confidence: 91%
“…Actually, search results in WoS are not presented by author, year, subject and document types like Scopus, but also by institutions and countries [ 32 ], which is convenient for scholars to analyze the distribution of the research organizations. Moreover, WoSCC has been used as a data source in some previous bibliometric studies [ 33 , 34 , 35 , 36 , 37 , 38 ], which further proves its feasibility especially in the natural science domains. The study design was shown in Figure 1 .…”
Section: Methodsmentioning
confidence: 91%
“…For example, Goerlandt et al [ 45 ] employed CiteSpace to conduct a co-citation analysis to reveal the knowledge base in the field of risk communication, while Zhao. et al [ 46 ] used CiteSpace to identify popular research issues and future research directions in the field of human health and climate change.…”
Section: Methodsmentioning
confidence: 99%
“…This paper uses bibliometrics to count the number of publications each year and uses an exponential function to fit ( Figure 2 ) [ 45 ]. From 1990 to 2020, the number of publications in the field of health technology increased exponentially.…”
Section: Resultsmentioning
confidence: 99%